If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + 3a + 12 = 36 Reorder the terms: 12 + 9a + 3a = 36 Combine like terms: 9a + 3a = 12a 12 + 12a = 36 Solving 12 + 12a = 36 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12a = 36 + -12 Combine like terms: 12 + -12 = 0 0 + 12a = 36 + -12 12a = 36 + -12 Combine like terms: 36 + -12 = 24 12a = 24 Divide each side by '12'. a = 2 Simplifying a = 2
| -5+7(k+6)=93 | | 6(-p)=54 | | x^2+4x+2=5x+7 | | -2m+19= | | 35+80h=915 | | 73-17=46+7 | | -9(8-9m+n)= | | 3x^3-4x^3= | | -4(7v-7)+5v=-87 | | 2x^2-20x+100=108 | | 5x+3y+2z=4 | | 2(10)+3y=24 | | 2(x+3y)+4(x+5y)-3x= | | (42+2x)=(3x+4) | | 2(10.4)+3y=24 | | -2(y-3)=-6y-12+2y | | 3a+12a=-7 | | 7.5a+9.2-6.8a-11b= | | -6(-1-3x)=-120 | | 9x^3+54x^2= | | 9x+3x=24 | | 4(2y-10)=3(2y+8) | | 3(5x+1)-2=3y+6 | | -2(y-3)=-6y-12+12y | | 4x-9y+3x= | | 3(y-10)+1=-5.5(y-8) | | X^2-5-35=0 | | -9(x-6)-4=50 | | -10x=-27x-17 | | x+3(1.25)=7.25 | | (4a-3b)(2a+6b)= | | 5xt-3xy= |